Glial Fibrillary Acidic Protein (GFAP): Neuroinflammation Biomarker in Acute Ischemic Stroke - Amalia L (Dove Medical Press, 2021)
Lisda Amalia Department of Neurology, The First Affiliated Hospital of Faculty of Medicine, Universitas Padjadjaran/RSUP dr. Hasan Sadikin, Bandung, IndonesiaCorrespondence: Lisda Amalia Jl.Pasteur 38, Bandung, 40161, IndonesiaEmail dr.lisda@gmail.comIntroduction: Blockage of the cerebral arteries due to thrombosis and embolism resulting in decreased blood flow to the brain, reduced oxygen supply to the brain, resulting in neuronal damage and causes astrocyte cells to secrete glial fibrillary acidic protein (GFAP). The objective of this study was to determine the correlation between GFAP levels serum and clinical outcome in patients with acute ischemic stroke.Methods: This was observational with a cross-sectional design on acute ischemic stroke patients confirmed by CT scans and divided into large vessel occlusion and small-vessel occlusion. Clinical outcome was measured using the National Institutional Health Stroke Scale (NIHSS) tool. Statistical analysis uses Spearman's rank correlation test and Mann Whitney's test, significant if p < 0.05.Results: After collecting 33 research subjects, we found 16 people with large vessel occlusion and 17 people with small vessel occlusion. Serum GFAP levels were 0.2- 1.9 ng/mL, 9.1% with a mild neurological deficit, 45.45% were moderate neurological deficits, and 45.45% were severe neurological deficits. There was a significant positive correlation (r = 0.522; p = 0.002) between serum GFAP levels and the degree of neurological deficit in ischemic stroke patients. There was a statistically significant difference between serum GFAP levels in ischemic stroke patients with CT scan results of large artery occlusion compared to small artery occlusion (0.7 vs 0.4ng/mL; p = 0.001).Conclusion: There was a positive correlation between GFAP level serum and NIHSS score on acute ischemic stroke. The higher the value of GFAP serum level, the higher the value for NIHSS and correlated with stroke severity and the extent of brain damage in ischemic stroke patients.Keywords: GFAP, clinical outcome, acute ischemic stroke, small vessel occlusion, large vessel occlusion